Ag/Fe3O4-N-Doped Ketjenblack Carbon Composite as Highly Efficient Oxygen Reduction Catalyst in Al-Air Batteries. Issue 14 (1st January 2017) - Li, Fuzhi; Fu, Liang; Li, Jingsha; Yan, Jun; Tang, Yougen; Pan, Yingfeng; Wang, Haiyan
Abstract : Highly efficient and low-cost catalysts are greatly desirable for oxygen reduction reaction (ORR) to replace the costly Pt/C. Here, we report a novel Ag/Fe3 O4 -N-doped ketjenblack carbon (KB) composite synthesized by a facile and scalable strategy using silver nitrate, iron nitrate, glucose, urea and KB as raw materials. This method involves an initial one-pot hydrothermal treatment and the subsequent pyrolysis process as well as hydrochloric acid treatment. The as-prepared composite with a low Ag mass ratio of 4.22% shows excellent catalytic activity toward ORR in alkaline solution (half wave potential of 0.82 V, limiting current density of 6.0 mA cm −2 ). The half-wave potential is only 8.2 mV negative shift after 2000 cycles, even better than the 20% Pt/C, demonstrating remarkable stability. When used as cathode catalyst in home-made Al-air battery, this composite shows a higher discharge voltage of 1.49 V at a current density of 50 mA cm −2 than that of Pt/C (1.45 V). This superior performance should be attributed to the synergistic effects of Ag nanoparticles, carbon surrounded Fe3 O4, Fe-N active sites and N-doped KB.